The Diane Goode book of American folk tales & songs - Goode, Diane; Durell, Ann. (New York : E.P. Dutton, 1989)
Presents a collection of folk tales and songs from a variety of regions and ethnic groups in the United States.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
4.8
K-3
Keywords: Tales -- United States; Folk songs, English -- United States -- Juvenile literature; Folklore -- United States; Folk songs, English -- United States; Folklore -- United States; American folk songs; Tales -- United States; Folk songs, English; Folklore -- United States